Zero Trust and Cloud Identity: Building a Resilient Security Framework - Naga Yeswanth Reddy Guntaka (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the implementation of Zero Trust Architecture (ZTA) and cloud identity solutions in building resilient security frameworks for modern enterprises. As traditional perimeter-based security models become inadequate, organizations are shifting towards identity-centric approaches that incorporate continuous verification and least privilege access principles. It examines the evolution of identity management, emphasizing the transformation towards decentralized identity systems and their integration with established security frameworks. Through analysis of current standards and best practices, including NIST guidelines and industry frameworks, the article presents comprehensive strategies for implementing Zero Trust principles alongside modern Identity and Access Management (IAM) solutions. It encompasses critical components such as identity governance, role-based access control, micro-segmentation, and automated policy enforcement. The article also addresses implementation challenges, providing a phased approach for organizations transitioning to Zero Trust Architecture while maintaining operational efficiency. Additionally, the article explores emerging trends and preparation strategies, offering insights into future considerations for maintaining robust security postures in an evolving threat landscape.